1988
DOI: 10.1029/jb093ib03p02053
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity of the Caribbean‐Nazca Boundary: Constraints on microplate tectonics of the Panama region

Abstract: There are at least three kinds of models that have been used to explain plate motions and boundaries in the Panama region. These models suggest that the major Caribbean‐Nazca boundary is (1) a thrust fault along which the Panama Deformed Belt has developed, (2) a left‐lateral strike‐slip fault along the southern margin of Panama, or (3) a diffuse array of mostly thrust faults which cause internal deformation to occur throughout Panama. In this paper, we use joint epicenter location methods to obtain improved l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
10

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 34 publications
1
35
0
10
Order By: Relevance
“…To the north, the Caribbean plate is bounded by the Oriental and Septentrional faults and the Puerto Rico trench; while to the south the Caribbean plate is bounded by a dextral strike-slip fault zone, the El Pilar-Central Range fault zone [Jordan, 1975;Adamek et al, 1988;Holcombe et al, 1990;Mascle and Letouzey, 1990;Pindell and Barrett, 1990;Heubeck and Mann, 1991;Mann et al, 1995;Flinch et al, 1999;Weber et al, 2001].…”
Section: Tectonic Setting Of the Lesser Antilles Arc In The Caribbeanmentioning
confidence: 99%
“…To the north, the Caribbean plate is bounded by the Oriental and Septentrional faults and the Puerto Rico trench; while to the south the Caribbean plate is bounded by a dextral strike-slip fault zone, the El Pilar-Central Range fault zone [Jordan, 1975;Adamek et al, 1988;Holcombe et al, 1990;Mascle and Letouzey, 1990;Pindell and Barrett, 1990;Heubeck and Mann, 1991;Mann et al, 1995;Flinch et al, 1999;Weber et al, 2001].…”
Section: Tectonic Setting Of the Lesser Antilles Arc In The Caribbeanmentioning
confidence: 99%
“…They are conelated with the formation of a postcollision Panama microplate (Fig. 1) that was detached from the Caribbean plate in the north by the convergent North Panama deformed belt (Adamek et al, 1988) and from the Nazca plate to the south Geological Society of America Bulletin, November/December 2004 1341 by the South Panama deformed belt (Mann and Kolarsky, 1995 (Mann and Kolarsky, 1995). Furthermore, Kellogg and Vega (1995) and Trenkamp et al (2002), using global positioning system measurements, have indicated that the Panama microplate is now acting as a rigid indenter with respect to South America.…”
Section: Syn-and Postcouisional Eventsmentioning
confidence: 99%
“…Esto incluye los sismos superficiales (< 30 km) ocurridos dentro de la placa Caribe y la microplaca de Panamá y en las fallas del Cinturón Deformado del Norte de Panamá (e.g. Adamek et al, 1988) y Cinturón Deformado del Centro de Costa Rica (e.g. Marshall et al, 2000).…”
Section: Distribución Por Origenunclassified